An electrochemiluminescence sensor based on CdSe@CdS functionalized MoS2 and hemin/G-quadruplex-based DNAzyme biocatalytic precipitation for sensitive detection of Pb(ii). Issue 1 (6th December 2017) - Du, Xiao-Li; Kang, Tian-Fang; Lu, Li-Ping; Cheng, Shui-Yuan
Abstract : A novel electrochemiluminescence biosensor based on CdSe@CdS quantum dots functionalized MoS2 modified electrode was developed for sensitive detection of Pb(ii ) using HRP-mimicking DNAzyme biocatalytic reaction. Abstract : A novel electrochemiluminescence (ECL) biosensor based on CdSe@CdS quantum dots (QDs) functionalized MoS2 modified electrode was developed for sensitive detection of Pb(ii ) using HRP-mimicking DNAzyme biocatalytic precipitation (BCP) for ECL signal quenching. Polycationic poly(diallyldimethylammonium chloride) (PDDA) and negatively charged QDs were adsorbed on the surface of MoS2, in sequence, to form the MoS2 –QDs composites, which were employed as a matrix for the immobilization of the G-rich DNA strand, i . e ., T30695. The MoS2 –QDs were characterized by UV-vis absorption spectroscopy, fluorescence spectroscopy, energy dispersive spectrometry, transmission electron microscopy, and field emission scanning electron microscopy. CdSe@CdS QDs can produce an ECL signal using 0.1 M K2 S2 O8 as a co-reactant. T30695 can combine with Pb(ii ) ions to form a stable parallel G-quadruplex. The G-quadruplex can further combine with hemin to form DNAzyme, which can catalyze H2 O2 and oxidize 4-chloro-1-naphthol (4-CN) to produce an insoluble precipitation of benzo-4-chlorohexadienone on the surface of the sensor. When the concentration of Pb(ii ) in the solution was increased, more of DNAzyme was generated and subsequently more 4-CN molecules were oxidized catalytically, leading to a decrease of the ECL signal. Using this quenching strategy, the ECL signal of the biosensor was linearly dependent on the logarithm of the Pb(ii ) concentration ranging from 1.0 × 10 −15 to 1.0 × 10 −11 M with a detection limit of 0.98 f M. The stability and selectivity of the sensor were also investigated. The sensor was applied in the determination of Pb(ii ) in the real water samples and satisfactory results were obtained.